The Impact Of Post-Competitive Sleeping Hours On The Sleep Quality Of Female Pencak Silat Athletes - Hartanto, Jasmine Rizki Putri; Fitri, Mustika; Williyanto, Septian (STKIP PGRI Jombang, 2023)
This research is motivated by the large number of pencak silat athletes who pay less attention to the quality of their sleep after competing. As a result of these issues, the aim of this study is to find out how the quality of sleep and sleep habits of athletes in the post-competition stage have an impact on the performance and psychology of pencak silat athletes in the future and how important it is for athletes to maintain good sleep quality in order to maintain their post-martial arts achievements competition. This study used a qualitative correlation technique using a PSQI (the Pittsburgh Sleep Quality Index) questionnaire distributed via a Google Form. The people who participated in this study were female pencak silat athletes from several areas in West Java from different clubs or universities, for a total of 46 persons who were consequently rejected by 6 people, which resulted in 40 female pencak silat athletes. The technique used for sampling is Non-random sampling is also called probability sampling. Based on the results of the study, it was stated that there was a positive relationship between hours of sleep after competition and the sleep quality of female pencak silat athletes, The results reveal a significance level of <0.05 based on the linear test and single correlation using the SPSS 25 application. The conclusions from this study conclude that the good or bad hours of sleep of athletes after competition can impact their quality of sleep in the next competition.